2005
DOI: 10.1111/j.1365-2443.2005.00851.x
|View full text |Cite
|
Sign up to set email alerts
|

The GTP binding protein Obg homolog ObgE is involved in ribosome maturation

Abstract: Obg proteins belong to a subfamily of GTP binding proteins, which are highly conserved from bacteria to human. Mutations of obgE genes cause pleiotropic defects in various species but the function remained unclear. Here we examine the function of ObgE, the Obg homolog in Escherichia coli . The growth rate correlates with the amount of ObgE in cells. Co-fractionation experiments further suggest that ObgE binds to 30S and 50S ribosomal subunits, but not to 70S ribosome. Pull-down assays suggest that ObgE associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
169
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(177 citation statements)
references
References 60 publications
(69 reference statements)
6
169
2
Order By: Relevance
“…Both E. coli and C. crescentus have been reported to copurify with the ribosome, although this interaction has been reported to be weak (for Caulobacter) (Lin et al, 2004) or variable (for E. coli ) (Kobayashi et al, 2001;Sato et al, 2005). It has been suggested that ObgE is required for ribosome biogenesis and that observed cell cycle effects may be an indirect consequence of loss of translation capacity (Sato et al, 2005).…”
Section: Obge Depletion Does Not Reduce Translational Capacitymentioning
confidence: 99%
See 2 more Smart Citations
“…Both E. coli and C. crescentus have been reported to copurify with the ribosome, although this interaction has been reported to be weak (for Caulobacter) (Lin et al, 2004) or variable (for E. coli ) (Kobayashi et al, 2001;Sato et al, 2005). It has been suggested that ObgE is required for ribosome biogenesis and that observed cell cycle effects may be an indirect consequence of loss of translation capacity (Sato et al, 2005).…”
Section: Obge Depletion Does Not Reduce Translational Capacitymentioning
confidence: 99%
“…Previous studies of Obg orthologues have examined different temperature-sensitive alleles and point mutations to deplete functional Obg in Gram-negative bacteria (Kobayashi et al, 2001;Datta et al, 2004;Sato et al, 2005;Sikora et al, 2006). The results of these studies have suggested various and diverse cellular roles, including ribosome biogenesis, stress response and chromosome segregation.…”
Section: Obge Is Necessary For Efficient Chromosome Partitioningmentioning
confidence: 99%
See 1 more Smart Citation
“…Both proteins have a binding site on ribosomes, and they could interact with L23, a ribosomal protein on the peptide exit tunnel of ribosomes (Gu et al, 2003). Era, ObgE, SelB, and YchF could also interact with ribosomes (Sayed et al, 1999;Leipe et al, 2002;Sato et al, 2005). The binding of these GTPases to ribosomes reduced the amount of dissociated proteins, which could improve denatured citrate synthase refolding, thereby decreasing the reactivation level.…”
Section: Discussionmentioning
confidence: 99%
“…The other motifs indicate GTP binding, GTPase, methyltransferase, peptidyl-prolyl isomerase, helicase activities, and chaperone function. These proteins may have roles in ribosome maturation or assembly, RNA folding, rRNA processing, protein assembly, and subunit structure stabilization similar to what has been observed in other organisms (41)(42)(43)(44)(45)(46)(47)(48)(49). Intriguingly helicase activity was recently identified in ribosomes that could account for its ability to translate through downstream mRNA secondary structure (50).…”
Section: Sequence Characteristics Of Mt Ribosomal Proteins-mostmentioning
confidence: 99%